COMMUNION ECCLESIOLOGY IN A RACIALLY POLARIZED SOUTH AFRICA - I. Nell (Acta Theologica)
Review of the book: K.T. Resane, (Bloemfontein:SUN MeDIA, 2017). 285 pp. Paperback. ISBN 978-1-920382-96-4, R365.